Factor Affecting Environmentally Responsible Behaviors of Secondary school Student 3 under the Office of Secondary Educational Service Udon Thani: Factor Affecting Environmentally Responsible Behaviors of Secondary school Student 3 under the Office of Secondary Educational Service Udon Thani - Danoi, Patcharin; Surat, Maneeya (RATANABUTH JOURNAL, 2023)
The purposes of this study were 1) to study the level of student’s environmentally responsible behaviors and the level of the factors effecting on student’s environmentally responsible behaviors 2) to study the relationships between the factors effecting and student’s environmentally responsible behaviors 3) to study the factors effecting on student’s environmentally responsible behaviors and make the equation for prediction student’s environmentally responsible behaviors. The samples were 420 students from secondary school under the Office of Secondary Educational Service Udon Thani. Data collected by the rating scale questionaries and the environmental knowledge test. The data were analyzed by Mean, Standard Deviation, Pearson’s product moment correlation coefficient and Multiple regression analysis. The results were as follows: 1) The secondary 3 school students under the office of Secondary Educational Service Udon Thani had environmentally responsible behaviors at moderate level. They had environmentally responsible behaviors in resource actions at high level. Citizenship actions, consumption, instrument usings, waste reductions and environmental activities in moderate level. As for the level of factors affecting students’ environmental responsibility behaviors, Overall, it was at a high level. 2) Environmental attitude, self-efficacy, intrinsic motivation, getting social support, future orientation and self-control, internal locus of control, environmental knowledge has positive relations with student’s environmentally responsible behaviors under the Office of Secondary Educational Service Udon Thani at 0.05 significance level. When analyzes the correlation coefficient between the predictor and student’s environmentally responsible behaviors, the range of the correlation coefficient was between 0.54 - 0.79 3) The factors that affected student’s environmentally responsible behaviors under the Office of Secondary Educational Service Udon Thani at 0.05 significance level. Were internal locus of control, Environmental attitude, environmental knowledge, intrinsic motivation, getting social support, self-efficacy and future orientation and self-control respectively. That could predict at 80 percent.